The IMSI Procedure Improves Laboratory and Clinical Outcomes without Compromising the Aneuploidy Rate When Compared to the Classical ICSI Procedure - Daniel Luna; Roly Hilario; Julio Dueñas-Chacón; Rocío Romero; Patricia Zavala; Lucy Villegas; Javier García-Ferreyra (SAGE Publishing, 2015)
Purpose The intracytoplasmic morphologically selected sperm injection (IMSI) procedure has been associated with better laboratory and clinical outcomes in assisted reproduction technologies. Less information is available regarding the relationship between embryo aneuploidy rate and the IMSI procedure. The aim of this study is to compare the clinical outcomes and chromosomal status of IMSI-derived embryos with those obtained from intracytoplasmic sperm injection (ICSI) in order to establish a clearer view of the benefits of IMSI in infertile patients. Methods We retrospectively analyzed a total of 11 cycles of IMSI and 20 cycles of ICSI with preimplantation genetic diagnosis. The fertilization rate, cleavage rate, embryo quality, blastocyst development, aneuploidy rate, pregnancy rate, implantation rate, and miscarriage rate were compared between the groups. Results Similar rates of fertilization (70% and 73%), cleavage (98% and 100%), and aneuploidy (76.9% and 70.9%) were observed in the IMSI and ICSI groups, respectively. The IMSI group had significantly more good quality embryos at day 3 (95% vs 73%), higher blastocyst development rates (33% vs 19%), and greater number of hatching blastocysts (43% vs 28%), cycles with at least one blastocyst at day 5 (55% vs 35%), and blastocysts with good trophoectoderm morphology (21% vs 6%) compared with the ICSI group ( P < 0.001). Significantly higher implantation rates were observed in the IMSI group compared with the ICSI group (57% vs 27%; P < 0.05). Pregnancy and miscarriage rates were similar in both groups (80% vs 50% and 0% vs 33%, respectively). Conclusion The IMSI procedure significantly improves the embryo quality/development by increasing the implantation rates without affecting the chromosomal status of embryos. There is a tendency for the IMSI procedure to enhance the pregnancy rates and lower the miscarriage rates when compared with ICSI.